Protein dysregulation during Leishmania infantum infection in anti-TNF immunosuppressed mice revealed through quantitative proteomics analysis of extracellular vesicles - Lorena Bernardo; Lorena Bernardo; Ana Montero-Calle; Jose Carlos Solana; Jose Carlos Solana; Marina Lozano-Rendal; Ana Torres; Ana Torres; Carmen Sánchez; Rodrigo Barderas; Rodrigo Barderas; Javier Moreno; et al. (Frontiers in Immunology)
IntroductionVisceral leishmaniasis (VL) occurs more frequently in immunosuppressed individuals, especially those undergoing immunosuppressive drug therapy for an autoimmune disease. In those receiving TNF antagonist therapy (anti-TNF), the course of VL is more severe and the response to traditional leishmanicidal treatments, such as antimonials (Sb), is often reduced. This effect of anti-TNF treatment is observed in our immunosuppressed-mouse model of VL. In this model, we compared anti-TNF immunosuppression with no immunosuppression before and after VL treatment with Sb.MethodsSerum-derived extracellular vesicles (EVs) were analyzed through label-free quantitative proteomics to identify proteins involved in both VL severity and the impact of anti-TNF immunosuppression on treatment outcome.ResultsIn total, 223 dysregulated proteins were found in the pre-treatment groups, the majority of which, such as vitronectin, haemopexin or caveolin-1, were downregulated in the anti-TNF samples. In contrast, 173 proteins were identified in the Sb-treatment groups, most of which were found enriched in the anti-TNF plus treatment samples (anti-TNF+Sb) including fibronectin, transferrin, vitronectin and dipeptidyl peptidase-4. These differentially-expressed proteins were associated with pathways related to the immune system, liver regeneration, and ion transport.ConclusionOur findings have useful implications for the clinical management of VL patients under anti-TNF immunosuppression.